A strategy for introducing diagnostic reasoning: hypothesis testing using a simulation approach. - Plunkett EJ; Olivieri RJ (Nurse Educator)
The ability to generate a number of hypotheses, so all possibilities in a situation are recognized, is a vital component in arriving at a correct nursing diagnosis. Students need learning experiences in this aspect of the diagnostic reasoning process. The authors discuss the four phase simulation method of teaching, which provides a useful model for developing beginning skills in hypothesis generation.